Power and Silence: Constitutional and Institutional Reforms to Address Sexual Violence in Indonesian Higher Education - Muhtar Said; Fira Mubayyinah; Muhammad Adib Alfarisi; Ali Akhbar Abaib Mas Rabbani Lubis (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2026)
Why do comprehensive legal reforms fail to provide consistent protection for survivors of sexual violence in higher education? This article addresses this question through a qualitative doctrinal legal study informed by a Foucauldian perspective on the power relations. This analysis draws on primary legal materials, including the 1945 Constitution of the Republic of Indonesia, Law No. 12 of 2012 on Higher Education, Minister of Education, Culture, Research, and Technology Regulation No. 30 of 2021, and Law No. 12 of 2022 on Sexual Violence Crimes, complemented by relevant secondary legal materials. The findings demonstrate that Indonesia has developed an integrated legal framework that combines constitutional guarantees, higher education governance, administrative regulations, and criminal law. However, the effectiveness of this framework is shaped by institutional authority, academic hierarchy, disciplinary mechanisms, and living law, which collectively influence reporting practices, institutional accountability, and victim protection. This article argues that inconsistencies in institutional responses are explained not simply by the scope of statutory regulation but by the interaction between formal law, power relations, and living law operating within higher education institutions. By extending the concept of living law beyond its conventional association with local communities to modern organizations, this study offers a conceptual framework for understanding how legal authority acquires practical meaning in institutions.